A inserção do contrato coletivo de trabalho transnacional no plano supralegal da ordem jurídica brasileira - Cordeiro, Wolney de Macedo (2013)
This doctoral thesis deals with the question of labour regulation in a social structure characterised by postmodern mitigation of statehood. Analyzing private instruments of labour regulation, it was identified as the thesis s problem the procedures in which such documents may be inserted in Brazilian legal system. In confronting the defined problem, it was demonstrated the feasibility of embedding these structures of private regulation through a procedure analogous to the reception of international treaties on human rights as a supralegal status. By applying the deductive method, the thesis was built upon confronting the structure of postmodern social environment with its characteristic contingency, to the feasibility coexistence of private regulation instruments in the Brazilian legal framework. Alongside clearly outlining the main features of the postmodern society, it was analyzed how strongly Westphalian parameters were influenced by transversality, fragmentation and presence of private and quasi-private actors. From the evaluation of the relationship between national and international regulatory frameworks, it was concluded that the postmodern social structure bequeathed several non-linear movements between these two normative standards, which cannot be separate as isolated compartments. This change in the structure of the private relations regulations also showed significant effects on the regulation of social issues. Given the characteristics of postmodern society, this subject showed incipient, rhetorical and ideological responses, respectively from supranational and integration law, corporations codes of conduct and global unions. After having observed the inadequacy of orthodox responses, it became imperative to build a conceptual private framework able to be assimilated by domestic law. Accordingly, from the observation of the congruent characteristics of these various regulatory manifestations, it is possible to identify the transnational collective agreement concept as the agreement related to private or quasiprivate actors, designed to regulate social issues in a transnational environment. The transnational collective agreement, as conceptual category recognized, demands the identification of assumptions and requirements suitable to enable their assimilation before the Brazilian legal system. Using, as reference, the postulates about the assimilation of international law in the Brazilian domestic law, and especially the construction of the supralegalidade concept about international treaties on human rights (CF, art. 5th, §§ 2nd and 3rd), it is possible to identify benchmarks reception of labour transnational collective agreement. Being recognized the domestic erga omnes effects of collective bargaining agreements, produced by the private action of unions, identical treatment may be given to labour transnational collective agreement. Just as it operates in relation to the internal instruments of collective bargaining, transnational collective agreements must be assimilated from the observance of in abstracto and in concreto requirements, especially regarding a broader and more effective labour protection.